Employee Loyalty is Reviewed from Emotional Intelligence, Commitment and Self Efficacy (Case Study at Diponegoro National Hospital Semarang) - Suryawardana, Edy; Ariefiantoro, Teguh; Hidayah, Nining (Universitas Negeri Semarang, 2021)
The purpose of conducting this research is to determine the effect of emotional intelligence, commitment and self-efficacy on employee loyalty at the Diponegoro National Hospital, Semarang. This research is a quantitative study 215 respondents. Data collection system using a questionnaire. This research uses the classical assumption test, multiple linear regression analysis, t test, F test, and the coefficient of determination test. The results of the F (simultaneous) test show that employee loyalty is significantly influenced by emotional intelligence, commitment and self-efficacy simultaneously. While the t test (partial) shows that employee loyalty at the Diponegoro National Hospital Semarang is negatively and significantly affected by emotional intelligence while commitment, self-efficacy, and competence have a positive effect on employee loyalty at the Diponegoro National Hospital Semarang individually (partial).